Factors Associated With Positive Screens on the Mood Disorder Questionnaire in Primary Care - Gorski, Eugene (Physicians Postgraduate Press, Inc., 2006)
Objective: This article examines the prevalence of positive testing for bipolar tendencies on the Mood Disorder Questionnaire (MDQ) in a primary care office setting. Method: Participants in this study were older than 18 years of age and had not been previously diagnosed with bipolar disorder at the time of study participation. 688 individuals submitted appropriately completed forms and were included in the study, which was conducted from October through November 2004. Results: 10.8% of screened individuals tested positive for bipolar tendencies using the criteria determined by the investigators. These findings exceed estimates in previous studies of the prevalence of bipolar disorder in the general population. Statistically significant predictors of MDQ results included age (< 35 or ≥?35 years), complaints of anxiety or depression, and psychotropic medication use (none, 1 or more). Study participants who were under 35 years of age and complained of anxiety or depression and took 1 or more psychotropic medications had a probability of testing positive on the MDQ of 0.45. Those under the age of 35 years who complained of anxiety or depression and had no history of psychotropic medication use had a probability of testing positive on the MDQ of 0.27. The sample group consisting of individuals aged 35 years or older who complained of anxiety or depression and took psychotropic medications yielded a probability of positivity of 0.30; the probability of positivity for the 35-and-over subgroup who complained of anxiety or depression but did not take psychotropic medications was 0.16. Conclusion: Participants who did not complain of anxiety or depression and did not have a history of psychotropic medication use exhibited a lower incidence of positive MDQ scores compared with those who did complain of anxiety and depression and did have a history of psychotropic medication use. No other correlations were found to be statistically significant. No separate validation of the MDQ results cited was independently performed during this study.